(NkRIOGENNO(B-(N\OLOWYE OTLOVENIQ wOSTO^NOJ aRKTIKI I sUBARKTIKI (B/s - (NtOMIRDIARO(B, (NsAWELIJ wLADIMIROWI^s; (N~ERNENXKIJ(B, (NbORIS iWANOWI^s; (NbISK\(B, (Ns(B.(Nf(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 193-197s
(Nan sssr(B, (NdALXNEWOST(B. (NNAU^(B. (NCENTR(B, (NsEW(B.-(NwOST(B. (NKOMPLEKS(B. (Nniis
Keywords: (NaRKTIKAs; (NsUBARKTIKIs; (N|OLOWYE OTLOVENIQs